2021
DOI: 10.1111/jcmm.16368
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis‐related gene signature as a prognostic marker for lower‐grade gliomas

Abstract: Ferroptosis is a newly discovered form of programmed cell death, which has unique biological effects on metabolism and redox biology. In this study, the prognostic value of ferroptosis‐related genes was investigated in lower‐grade gliomas (LGG). We downloaded the ferroptosis‐related genes from the FerrDb dataset. Univariate Cox and LASSO regression analyses were applied to identify genes correlated with overall survival (OS). Subsequently, 12 ferroptosis‐related genes were screened to establish the prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…For example, Zhu et al demonstrated the utility of a 4-FRGs model in predicting the prognosis of esophageal adenocarcinoma (38). Zheng et al developed a 12-FRGs model to better predict the prognosis of patients with lower-grade gliomas (39). Jiang and his colleagues constructed an eight-gene ferroptosis-related prognostic model to predict the prognosis of gastric cancer patients (40).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhu et al demonstrated the utility of a 4-FRGs model in predicting the prognosis of esophageal adenocarcinoma (38). Zheng et al developed a 12-FRGs model to better predict the prognosis of patients with lower-grade gliomas (39). Jiang and his colleagues constructed an eight-gene ferroptosis-related prognostic model to predict the prognosis of gastric cancer patients (40).…”
Section: Discussionmentioning
confidence: 99%
“…By integrating different independent prognostic factors, the nomogram can predict the possibility of an event outcome, such as the possibility of death or disease recurrence [ 17 ]. Several ferroptosis-related gene nomograms for predicting prognosis have been established for various types of cancer [ 18 , 19 ]. Zheng et al [ 18 ] developed a 12-FRG signature to predict the OS of patients with lower-grade gliomas, which showed a favorable predictive capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Several ferroptosis-related gene nomograms for predicting prognosis have been established for various types of cancer [ 18 , 19 ]. Zheng et al [ 18 ] developed a 12-FRG signature to predict the OS of patients with lower-grade gliomas, which showed a favorable predictive capacity. Based on the signature and clinicopathological features, they established a nomogram for predicting 1-, 3-, and 5-year OS.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the establishment of cancer prognostic models has been a mainstream of tumor research. For instance, Zheng et al (2021) identified 12 prognostic feature genes associated with ferroptosis in low level glioma. Jiang et al (2019) analyzed the glycolysis gene expression profiles of hepatocellular carcinoma and acquired a prognostic model based on metabolism-associated feature genes.…”
Section: Discussionmentioning
confidence: 99%